Identifikasi Karakter Morfologi dan Analisis Kandungan Nutrisi Buah Pisang Susu, Kepok, dan Raja Lokal Bali - Liran, I Gusti Putu Oka Maha Putra Wardana; Rai, I Nyoman; Mayadewi, Ni Nyoman Ari (Agrotrop : Journal on Agriculture Science; Vol 14 No 1 (2024), 2024)
Identificaion of Morphological Characters and Fruits Nutrient Analysis of Pisang Susu, Kepok, and Raja Lokal Bali. Banana ( Musa sp.) is one of the germplasms which is distributed in tropical and sub-tropical areas. Various types of bananas exist, causing differences in character between each cultivar. This research was carried out in July - October 2022. The location for sampling bananas was in Banjar Soka, Antap Village, Selemadeg Barat District, Tabanan Regency, while morphological identification and analysis of nutrient content were carried out at Laboratory. This study used UPGMA analysis and a completely randomized design (CRD) with three replications. Identification of morphological characters revealed differences in the qualitative characters of the shape of fruit, shape of the tip of fruit, rest of the flower relics, colour of the peel before and after ripening, cracking of the peel, surface of the peels, colour of pulp before and after ripening shape of the seeds, finger length, finger stalk length, finger stalk width and fruit peel thickness. The nutritional content of the fruit flesh is different in crude fat and crude fibre.